Analisis Sistem Dan Prosedur Pembayaran Tagihan Melalui Outlet Pospay (Sopp Pos) Guna Mendukung Pengendalian Internal (Studi Kasus Kantor POS Regional I Sumut) - Adinda Andi Putri, Fahresya Nur; Kusmilawaty, Kusmilawaty (Universitas Labuhanbatu, 2022)
One of the important goals of internal control is to create control both within a company or cooperative. In improving good systems and procedures. The purpose of this study was to determine the system and procedure for bill payment through pospay outlets (sopp pos) in supporting internal control. This research was conducted in a case study of the regional post office I of North Sumatra. This research uses descriptive qualitative method. Then, the researchers collected data by means of interviews, field observations, documentation, and literature studies to strengthen the data obtained. The results of this study are using pospay, the community can pay various bills and any installments, namely telephone bill payments, electricity bill bills (PLN), payment electricity tokens, drinking water bills (PDAM), insurance, credit installments (Finance), credit cards credit and personal loans, top-up credit, top-up funds, subscription television, and others.